VARIETIES OF NEOLOGISM USED IN ONLINE GAMING CONVERSATION - Matiini, Gharizi (Universitas Islam Sumatera Utara (UISU), 2024)
Neologism, a term used in linguistics, refers to the creation and definition of new lexical items with new meanings. It is frequently employed in specialized contexts, necessitating the development of new language forms. This study aims to investigate neologisms emerging from gaming language and identify the types that predominantly occur during gameplay. Given that online gaming became a popular pastime during the pandemic, observing the new language arising from in-game chat boxes is particularly intriguing. The study includes conversations from three participants playing three different online games, collected over one day of gameplay. The findings reveal that abbreviations, acronyms, and repurposed standard English terms are prevalent forms of neologisms in gaming language. Abbreviations like